Agro-Economic of Dusun Systems in Small Islands: A Case of Ambon City, Maluku Indonesia - Girsang, Wardis; Siregar, Adelina; Hamid, Hamid (Tropical Small Island Agriculture Management, 2024)
Whereas many studies highlight positive environmental and socio-economic effects of agroforestry systems, the agro-economic effect of Dusun practices as indigenous agroforestry systems has rarely been studied in detail, particularly in small island-Maluku Indonesia. This article examines the agro-economic of tropical perennial and annual fruit crops in the Dusun systems in Ambon city islands. A survey was conducted in three different Dusuns to obtain data through in-depth interviews of 88 heads of households. Our findings indicate that most Dusun farmers are uneducated and old age, half of them have small size of land, and 95% of land status belongs to kinship-clan ownership. Then, half of the farmers have an elementary school education, and 71% have a primary job as farmers, while 29% have a secondary job on the farm and non-farm activities. Amongst 26 crops that are found in three Dusun areas, nine crop types can be found in the whole Dusun, while the rest are located in one or two Dusun only. These crops are grown together and form multiple cropping structures from high stratum like durian and coconut to medium strata such as clove and nutmeg and low strata such as vegetables and tubers. The structures of the crops have an important role in maintaining biodiversity, minimizing soil erosion, water reservoir, and supporting socio-economic of the households. Annual income from rural household was estimated at around US$6487 or US $3.6/capita/day. Income average value was almost two folds of the World Bank poverty line standard. Nearly 80% of the total income are contributed by four main crops, i.e. clove (Eugenia aromaticum), durian (Durio zibethinus Mur), nutmeg (Myristica fragnans), and duku (Lansium domesticum), of which 11% is contributed predominantly by snake fruit (Salacca zallaca var amboniensis Becc), mangosteen (Garcinia mangostana L) and langsat (Lansium domesticum).